Analysis of Company Valuation and Factors of Goto Stock Price Decline After IPO - Holiawati; Yati Rosmiati, Dede; Eko Prasetyo; Kristiyanto; Wadi, Indra (Universitas Pamulang, 2025)
Startups in Indonesia have been growing very fast in recent years. The phenomenon of startups conducting IPOs on the Indonesian stock exchange is an interesting phenomenon that is worth discussing. Moreover, GOTO shares experienced sham price dynamics until a drastic decline since its opening in March 2022 until now. This research is a qualitative research with descriptive methods. The data source of this research is taken from primary data in the form of fundamental and technical analysis of GOTO shares and secondary data consisting of related journals, reports and company data as research data In analyzing the valuation of GoTo companies, researchers use the relative / market valuation method. The results showed that the valuation of GOTO shares when conducting an IPO was below the average valuation of world companies. The decline in stock prices that occurred after the IPO could be due to the fact that investors generally expect short-term profits on stocks that conduct IPOs. In addition, many investors make decisions to sell and buy based on stock price movements in the market and not based on company fundamentals. Suggestions to company management, investment managers, securities, and academics, to continue to educate investors regarding the valuation of e-commerce companies. Management should also consider share buybacks. For the next start-up management that will conduct an IPO, the company also needs to educate on company valuation, and prepare steps to maintain the stability of its share price after the IPO.